N6-methyladenosine modifications in maternal-fetal crosstalk and gestational diseases - Wu, Suqi; Liu, Ketong; Zhou, Bingyan; Wu, Suwen (Frontiers in Cell and Developmental Biology, 2023)
As a medium among pregnant women, environment and fetus, placenta owns powerful and delicate epigenetic processes to regulate gene expression and maintain cellular homeostasis. N6-methyladenosine (m6A) is the most prevalent modification that determines the fate of RNA, and its dynamic reversibility indicates that m6A may serve as a sensitive responder to environmental stimuli. Emerging evidence suggests that m6A modifications play an essential role in placental development and maternal-fetal crosstalk, and are closely related to gestational diseases. Herein, we summarized the latest techniques for m6A sequencing and highlighted current advances of m6A modifications in maternal-fetal crosstalk and the underlying mechanisms in gestational diseases. Therefore, proper m6A modifications are important in placental development, but its disturbance mainly caused by various environmental factors can lead to abnormal placentation and function with possible consequences of gestational diseases, fetal growth and disease susceptibility in adulthood.